2018
DOI: 10.1177/0269881118754710
|View full text |Cite
|
Sign up to set email alerts
|

Psychedelics and the essential importance of context

Abstract: Psychedelic drugs are making waves as modern trials support their therapeutic potential and various media continue to pique public interest. In this opinion piece, we draw attention to a long-recognised component of the psychedelic treatment model, namely ‘set’ and ‘setting’ – subsumed here under the umbrella term ‘context’. We highlight: (a) the pharmacological mechanisms of classic psychedelics (5-HT2A receptor agonism and associated plasticity) that we believe render their effects exceptionally sensitive to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
430
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 434 publications
(489 citation statements)
references
References 62 publications
26
430
1
Order By: Relevance
“…Recent work has consistently shown that the occurrence of mystical-type experiences is predictive of long-term therapeutic benefit from psychedelics (Maclean et al, 2011; Garcia-Romeu et al, 2014; Griffiths et al, 2016; Carhart-Harris et al, 2017, 2018; Roseman et al, 2018) and similar mechanisms may be at play in relation to improved mental well-being post NDE (Moody, 1975; Noyes, 1980; Ring, 1980; Groth-Marnat and Summers, 1998). It is pertinent to ask therefore, what common features shared between these states may be responsible for mediating the apparent long-term psychological benefits that follow them.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent work has consistently shown that the occurrence of mystical-type experiences is predictive of long-term therapeutic benefit from psychedelics (Maclean et al, 2011; Garcia-Romeu et al, 2014; Griffiths et al, 2016; Carhart-Harris et al, 2017, 2018; Roseman et al, 2018) and similar mechanisms may be at play in relation to improved mental well-being post NDE (Moody, 1975; Noyes, 1980; Ring, 1980; Groth-Marnat and Summers, 1998). It is pertinent to ask therefore, what common features shared between these states may be responsible for mediating the apparent long-term psychological benefits that follow them.…”
Section: Discussionmentioning
confidence: 99%
“…As both psychedelics and the NDE phenomena appear to be strongly influenced by contextual factors (Kellehear et al, 1994; Carhart-Harris et al, 2018), it could be argued that significant differences may exist regarding phenomenological features between both experiences. Nonetheless, considering the strong overlap on the items of the NDE scale, the study of such differences might require the use of other methods addressing nuances not explored here (e.g., the use of questionnaires addressing contextual factors and qualitative studies).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations